Analisis Pendidikan Dan Kemiskinan Tingkat Kabupaten Di Sumatera Barat - Harimikhairul Annisa; Ariusni; Fandy Triawan (Universitas Negeri Padang, 2026)
This study aims to analyze the factors that influence education and poverty at the district level in West Sumatra Province. This study uses panel data regression analysis in the form of a simultaneous equation model using the Two Stage Least Square (TSLS) method. The results show that health, consumption, internet use, and poverty simultaneously influence education, while internet use, investment, population, and education influence poverty.